Research on Logistics Oriented Spatial Data Mining Techniques - Wang, Peng; Ma, Li; Xi, Yuanyuan; Jin, Lianhua (2009 International Conference on Management and Service Science, 2009)
Since 2000, logistics becomes a popular subject and logistics industry becomes one of developed industries to government at all levels. Whatever on its operation level, management level or strategic level, logistics has a strong trend to use spatial data mining technology as one of its foundations. There are massive data information and much implicit and valuable knowledge in the database of logistics oriented GIS database. However, presently GIS is mainly limited to the collection, query, and statistic of data, so it can not discover effective relations and rules. We can mine massive spatial data which managed by GIS, analyze GIS data at higher level, and discover the important knowledge by the combination of data mining and GIS. The paper opens a new way for the development of logistics industry through knowledge discovery and data mining, associates GIS component MapX, offers a spatial data mining system architecture based on the MapX, and realizes model data preprocessing.